2006
DOI: 10.1007/s10840-006-8263-x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous alternans in Brugada ECG morphology

Abstract: A 23-year-old man presented with sick sinus syndrome and Brugada-like ECG pattern. Coved type ECG (type 1) converted to saddleback configuration (type 2) when R-R interval decreased and it changed to coved type pattern with increasing R-R cycle length. During stable heart rate, there was no change in Brugada ECG pattern. The R-R interval effect on these patterns can be explained by intensity or kinetics of ion currents and autonomic tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Decreased Na+ channel function has been suggested to be involved in the genesis of ST elevation in the right precordial leads, together with prominent development of the transient outward K+ current Ito in epicardial cells of the right ventricular outflow tract but with less or little development of current in endocardial cells resulting in augmented notch and loss of dome in epicardial action potential and increased disparity of repolarization. Fazelifar et al 3 reported that increased R‐R intervals led to a suppression of ICa, INa enhancing potassium current like Ito at the end of phase. In our case, no significant changes in R‐R intervals were noticed.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased Na+ channel function has been suggested to be involved in the genesis of ST elevation in the right precordial leads, together with prominent development of the transient outward K+ current Ito in epicardial cells of the right ventricular outflow tract but with less or little development of current in endocardial cells resulting in augmented notch and loss of dome in epicardial action potential and increased disparity of repolarization. Fazelifar et al 3 reported that increased R‐R intervals led to a suppression of ICa, INa enhancing potassium current like Ito at the end of phase. In our case, no significant changes in R‐R intervals were noticed.…”
Section: Discussionmentioning
confidence: 99%
“…1 B). This mechanism of alternans may account for TWA in patients with Brugada syndrome (12,(27)(28)(29)(30)(31)(32). The underlying dynamical mechanism by which I to promotes alternans has been revealed in our previous studies (36,54), in which we developed iterated map models to reveal the bifurcations leading to alternans and chaos.…”
Section: Computational Modelsmentioning
confidence: 99%
“…Furthermore, in most simulation and experimental studies, SDA has been shown to occur under fast pacing rates (7)(8)(9)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, in many clinical settings, TWA is usually observed in normal or slow heart rates, such as in patients with long QT syndrome (LQTS) (5,(24)(25)(26), Brugada syndrome (12,(27)(28)(29)(30)(31)(32), or heart failure (33,34). An important question arises: can SDA be a mechanism linking TWA to arrhythmogenesis under these clinical settings?…”
Section: Introductionmentioning
confidence: 99%
“…Впервые диагноз СБ был поставлен пробанду (III.23) в 2006г и был опубликован как изолирован-ное клиническое наблюдение [10]. Пробанд (III.23), мужчина в возрасте 23 лет, впервые обратился в клинику с жалобами на сердцебиение, одышку и эпизоды потери сознания, случавшиеся преиму-щественно в утренние часы.…”
Section: результатыunclassified